Zinner Syndrome: Case Series and Literature Review - D. A. Kushnerova; V. S. Tikhonova; I. A. Blokhin; A. P. Gonchar (SINAPS LLC, 2023)
Zinner syndrome is a rare congenital anomaly of the mesonephric duct, characterized by a triad of symptoms: seminal vesicle cysts, ipsilateral renal agenesis and ejaculatory duct obstruction. This leads to a severe complication - oligozoospermia/azospermia, which can subsequently cause infertility. The widespread use of medical imaging increases the probability of incidental detection. Namely, magnetic resonance imaging (MRI) is the imaging modality of choice for making a diagnosis.   Study purpose: to optimize patient routing in Zinner syndrome, as well as to minimize the risk of misdiagnosis or missed pathology, by providing strong and weak points for each modality.   Materials and methods: we present two clinical cases of Zinner syndrome.  The first one is a complicated course in a 25-year-old patient, and the second one is accidentally discovered in a 27-year-old patient. The patients underwent a comprehensive diagnostic panel, including: ultrasound (US), computed tomography (CT), magnetic resonance imaging (MRI). The results obtained were analyzed in the light of available literature data.   Results: in most cases, Zinner syndrome is an incidental finding during. The diagnosis based on these imaging methods and the correct patient routing allowed us to make a timely and correct diagnosis, followed by decisions on further treatment tactics.   Conclusion: Zinner syndrome is a rare disease and is often diagnosed based on imaging findings only. A radiologist and clinician need to know about the diagnostic criteria for this syndrome in order to successfully diagnose and determine the optimal treatment tactics.